HUBUNGAN TINGKAT PENDIDIKAN IBU DENGAN STATUS IMUNISASI BAYI DI WILAYAH KERJA PUSKESMAS BAHU KECAMATAN MALALAYANG - Tati S. Ponidjan (Jurnal Ilmiah Perawat Manado (Juiperdo), 2012)
The immunization program is one effort aimed at health care to reduce morbidity, disabilityand death from diseases preventable by immunization. Since the start of the immunizationprogram in Indonesia in 1956, currently has developed five types of mandatory vaccination(Immunisation Program Development / PPI are required), namely BCG, Hepatitis B, Polio,DTP and measles. While the recommended immunizations (Immunization Program Non-PPI)such as Hib, Penumokokus, influenza, MMR, Typhoid, Hepatitis A, Varicella, HPV. Theresults of the writer's observation in the region of shoulder health center, suggesting that arole in bringing the baby to be immunized is mostly done by the biological mother of a babywith a variety of educational levels, from elementary school through college.The purpose ofthis study was to determine the relationship of education level of mothers with infantimmunization status in the region of Sub Health Center Malalayang shoulders. This studyuses an observational analytic design, the approach Cross-Sectional. The research wasconducted in the region of Sub Health Center Shoulder Malalayang in December 2008 -January 2009. Samples were taken by sampling and obtained the total sample of 107respondents. The technique of collecting data through interviews. Data were analyzed usingchi-square test (X2), at 95% significance level (α = 0.05). The analysis using Chi Square test(X2) at 95% confidence level (α 0.05), a calculated value of 0.849 X2, X2 is smaller than thetable value of 5.591. P value obtained is equal to 0.654, is greater than α = 0.05. The resultsobtained in this study showed that there was no association with maternal education levelinfant immunization status in the Work Area Health Center District Malalayang Shoulders